Using a customer discovery process to enhance the potential dissemination and scalability of a family healthy weight program for rural communities and small towns - Gwenndolyn C. Porter; Jennie L. Hill; Kate A. Heelan; R. Todd Bartee; Caitlin A. Golden; Ali Malmkar; Bryce A. Abbey; Paul A. Estabrooks (BMC, 2024)
Abstract Aim Customer discovery, an entrepreneurial and iterative process to understand the context and needs of potential adoption agencies, may be an innovative strategy to improve broader dissemination of evidence-based interventions. This paper describes the customer discovery process for the Building Healthy Families (BHF) Online Training Resources and Program Package (BHF Resource Package) to support rural community adoption of an evidence-based, family healthy weight program. Methods The customer discovery process was completed as part of a SPeeding Research-tested INTerventions (SPRINT) training supported by the U.S. Centers for Disease Control and Prevention. Customer discovery interviews (n=47) were conducted with people that could be potential resource users, economic buyers, and BHF adoption influencers to capture multiple contextual and needs-based factors related to adopting new evidence-based interventions. Qualitative analyses were completed in an iterative fashion as each interview was completed. Results The BHF Resource Package was designed to be accessible to a variety of implementation organizations. However, due to different resources being available in different rural communities, customer discovery interviews suggested that focusing on rural health departments may be a consistent setting for intervention adoption. We found that local health departments prioritize childhood obesity but lacked the training and resources necessary to implement effective programming. Several intervention funding approaches were also identified including (1) program grants from local and national foundations, (2) healthcare community benefit initiatives, and (3) regional employer groups. Payment plans recommended in the customer discovery interviews included a mix of licensing and technical support fees for BHF delivery organizations, potential insurance reimbursement, and family fees based on ability to pay. Marketing a range of BHF non-weight related outcomes was also recommended during the customer discovery process to increase the likelihood of BHF scale-up and sustainability. Conclusions Engaging in customer discovery provided practical directions for the potential adoption, implementation, and sustainability of the BHF Resource Package. However, the inconsistent finding that health departments are both the ideal implementation organization, but also see childhood obesity treatment as a clinical service, is concerning.